Faktor-faktor Pemilihan Jasa Pelayaran di Surabaya - Devi Destiani Andilas; Andre Tanza; Yones Valencia (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2018)
The purpose of this study is to evaluate the main factor priority when selecting freight forwarder partnership of sea transport operator. Freight forwarder has function as the mediator of goods from producer to buyer which relies on sea transport operator. This study was using survey method of 100 freight forwarder companies associated of ILFA (Indonesian Logistics and Forwarder Association) located in Surabaya. The analysis was using statistic description of EFA (Exploratory Factor Analysis). The result shows that there are four factors affecting sea transport operator selection which are completeness of service facilities and reliabilities, international standard recognition, company’s reputation, and customers’ orientation.